A study on determining the presence of workplace discrimination against the Filipino LGBT youth - Jimenez, Christian Eligius A.; Epetia, Ma. Christina F. (Quezon City School of Economics, University of the Philippines Diliman, 2019)
Despite the increasing influence of the LGBT community in the economy, anecdotal evidence shows that discrimination based on their gender orientation still exists. We employ a logit regressions model to test the presence of workplace discrimination among the LGBT youth in the Philippines. Two indicators of discrimination are used in the study: income as an objective measure and self-reported workplace discrimination as a subjective measure. In contrast to anecdotal evidence, we find that discrimination based on gender orientation is insignificant in determining difference in income and the feeling of being discriminated in the workplace. Further analysis of the individual data provides other factors such as gender at birth, employment status, region, urban classification of the area of the respondent, and disability are significantly related to the two indicators of discrimination in the workplace. The significance of this study is to provide empirical analysis on the economic standing of Filipino LGBTs relative to their heterosexual counterparts, offering inputs to the policy agenda of inclusiveness and non-discrimination in the country.
Thesis (Master in Development Economics) -- University of the Philippines Diliman
Keywords: Sexual minorities -- Employment -- Philippines. -- Economic conditions; Sex discrimination -- Youth -- Philippines. -- Economic conditions; Gender mainstreaming -- Youth -- Philippines